2020
DOI: 10.1007/978-3-030-60124-9_12
|View full text |Cite
|
Sign up to set email alerts
|

Autowave Mechanics of Plastic Flow

Abstract: The notions of plastic flow localization are reviewed here. It have been shown that each type of localized plasticity pattern corresponds to a given stage of deformation hardening. In the course of plastic flow development a changeover in the types of localization patterns occurs. The types of localization patterns are limited to a total of four pattern types. A correspondence has been set up between the emergent localization pattern and the respective flow stage. It is found that the localization patterns are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 66 publications
(91 reference statements)
1
12
0
Order By: Relevance
“…The last provision needs to be clarified. As was established earlier [1], at the stage of linear strain hardening, the propagation speed of the phase autowave of localized deformation is given by the relation V aw ≈ /θ, in which the experimentally determined constant ≈ 5 • 10 −7 m/s [1,2]. Then, for the strain hardening coefficient, we can write…”
Section: Autowave Interpretation Of the Temperature Effect Of Plasticitymentioning
confidence: 77%
See 4 more Smart Citations
“…The last provision needs to be clarified. As was established earlier [1], at the stage of linear strain hardening, the propagation speed of the phase autowave of localized deformation is given by the relation V aw ≈ /θ, in which the experimentally determined constant ≈ 5 • 10 −7 m/s [1,2]. Then, for the strain hardening coefficient, we can write…”
Section: Autowave Interpretation Of the Temperature Effect Of Plasticitymentioning
confidence: 77%
“…Experimental studies and analysis of the kinetics of the solids plastic deformation development [1,2] shown that the essence of this process is the generation and regular evolution of a small set of autowave modes of macroscopically localized plastic flow, transforming into each other when the law of strain hardening changes during deformation. Autowave modes form the pattern of localized plasticity observed on the surface.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations